FORMULASI SEDIAAN KRIM WAJAH BERBAHAN AKTIF EKSTRA METANOL BIJI KAKAO NON FERMENTASI (Theobroma cacao L) KOMBINASI MADU LEBAH - Yumas, Medan (Balai Besar Industri Hasil Perkebunan, 2016)
Facial cream preparation contains active fotoprotector, antioxidant, and moisturizer derived fromnatural sources. Cocoa beans and honey bee are ones of anti-oxidant and moisturizer natural sourcescontaining polyphenol/phenolic and other flavonoid compounds. Flavonoid contains anti-oxidant agent asfree radical scavenger. The aim of this study was to obtain formula combination of non-fermented cocoabeans methanol extract and honey bee as active agents in effecting face skin moisturizing. Phases of theresearch consists of process of producing non-fermented cocoa beans methanol extract, producing facecream from non-fermented cocoa beans methanol extract and honey bee, and analysis on the characteristicsof the products. The result showed that face cream formulated from 1.56% of non-fermented cocoa beansmethanol extract and 2.34% of honey bee having 73.8% moisturizing effect in 60 minutes exposure doesnot irritate face skin and eyes. It has viscosity value 2.72 x 105 cps, has pH value 5.26 which is suitable withthe range of normal pH for skin (4.5-7.5), does not contain residues of nipasol and nipagin, has scoringaverage 1 â 2.9 by panelists on the attributes (aroma, consistency, texture, stickiness, homogeneoussensation, color, appearance, itchiness, erythema, easiness on cleaning, response on washing), and hastotal bacteria, khamir, and molod 5.0 x 102 which does not meet the requirements for skin moisturizer (SNI16-4339-1996) i.e. 102 colonies/gram.Keywords: non-fermented cocoa beans, honey bees, the active component, facial cream